Age-related differences in fitness performance and technical skills of young soccer players - Lipecki, K. (Polish Journal of Sport and Tourism, 2018)
Introduction. The aim of the study was to identify differences in the level of fitness and technical skills of young soccer players depending on age. Material and methods. The study examined 140 male elite soccer players from the Polish Sport Academy aged 12 to 18 years. Body mass, body height, fitness abilities (5-m, 10-m, and 30-m sprint; envelope run; standing long jump; pull-ups; and beep test) and technical skills (ball handling, juggling alternately with the leg and the head, short passes, and long passes) were measured. Results. Statistically significant (p < 0.05) differences indicating improvement with age were found in older players in speed (15.5%-18.8%), agility (5.7%), lower limb explosive power (39.4%), upper limb strength (254.3%), and cardiorespiratory endurance (31.9%). With regards to technical skills, the greatest progress was documented for long shots (passes) with the internal instep from the ground (140.6% for the dominant leg, DL, and 730.3% for the non-dominant leg, NDL). Slightly lower results were obtained for short shots (passes) with the central instep from the air (128% for DL and 103.6% for NDL) and short shots (passes) with the medial part of the foot (52.1% for DL and 82.8% for NDL), and the lowest were recorded for ball handling with direction change (32.3% for DL and 29.9% for NDL). Conclusions. In the process of talent identification and monitoring of training effects, coaches should take into account the differences in the rate of the development of fitness and technical skills of young athletes.